The Controversy of the Concept of Existence in Sufism: Tanaqud Al-Wujud as Negative Theology in Ibn Arabi's Thought - Aminim, Muhammad Ibnu (Universitas Islam Tribakti Lirboyo Kediri, 2025)
This article explores a central theme in Sufi tradition: the concept of wujūd (being), with a particular focus on the thought of Ibn Arabi. His metaphysical views are often regarded as paradoxical, giving rise to multiple interpretations, especially within the framework of negative theology, or tanāquḍ al-wujūd (the contradiction of existence). According to Ibn Arabi, the existence of God transcends the limits of human intellect, and any attempt to conceptualize the Divine inherently falls short. Thus, understanding true existence necessitates the rejection of fixed conceptual boundaries. This study also examines Ibn Arabi’s view of existence as a singular reality that lies beyond human description. This notion is foundational to his understanding of the relationship between God and the cosmos and reflects the core of his metaphysical system. Employing a qualitative method through a literature review of classical and contemporary sources, this research aims to analyze Ibn Arabi’s ontological paradigm critically. By doing so, the article contributes to a deeper understanding of the dialectic between the sacred and the secular within Sufi thought, offering insights into how Ibn Arabi’s mystical philosophy challenges conventional theological discourse.